Word of mouth on the Internet: Cross-cultural analysis - Mitić Sanja (Marketing (Beograd. 1991), 2020)
Development of the Internet and the technology of user generated content, allowed informal online communication between consumers (word of mouth). As the intensity of word of mouth on the Internet is growing, in terms of customers' comments, reviews on the products and services, and its potential influence on customer behaviour, this has become a contemporary topic in the literature. The topic of this paper is cross-cultural differences in generating word of mouth on the Internet. This paper aims to reveal main national cultural dimensions, in regard to Hofstede's and Globe project's methodology, that influence generating electronic word of mouth, on the sample of 15 European countries. The Western Balkans' and the East Europe's countries are included in the research, which was hard to find in different cross-cultural studies. The results show that members of individualistic cultures, where there is high uncertainty avoidance, as well as the members of cultures with high institutional collectivism, more often generate eWOM, in comparison to the members of collectivistic cultures, especially those with high in-group collectivism.